Utilisation of alcohol-related treatment after a first alcohol use disorder diagnosis in Hamburg, Germany - Jakob Manthey; Kilian Huß; Sven Buth; Ludwig Kraus; Anna Schranz; Carolin Kilian; Jürgen Gallinat; Ingo Schäfer; Bernd Schulte (European Psychiatry, 2025)
Abstract